Differentiation in police services in city neighborhoods - Spiegel, Uriel (Managing global transitions, 2014)
The demand for security depends on several socio economic characteristics such as income, property, family size that may affect the demand for pure public security or private security. In the case of a homogeneous population, the identical demands lead to an equal use of the shared public good along with an equal sharing of payments. In a heterogeneous population with a rectangular distribution of demands, security will be composed of both the pure equally shared public security along with private security that is paid individually and purchased in different quantities as a supplement to the pure public security. This combination could be applied permanently in order to achieve a social welfare improvement in comparison to the solely public security provided for the heterogeneous population.
Keywords: javno dobro; local public goods; heterogeneous customers; policijske storitve; varovanje; heterogeni kupci; police services